Exercise improves long-term social and behavioral rhythms in older adults: Did it play a role during the COVID-19 lockdown? - Giulia Cossu; Cesar Ivan Abbile Gonzalez; Luigi Minerba; Roberto Demontis; Massimiliano Pau; Fernanda Velluzzi; Caterina Ferreli; Laura Atzori; Sergio Machado; Dario Fortin; Ferdinando Romano; Mauro Giovanni Carta (SAGE Publishing, 2021)
The study aimed to verify whether exercise training in older adults can improve social behavioral rhythms (SBR) and if any modification is maintained over time. Older adults (n=120) from a previous randomized controlled trial, were randomly allocated to either a moderate-intensity exercise group or a control group. SBR was evaluated at t0, t26, and t48 weeks (during the COVID-19 lockdown), using the brief social rhythms scale (BSRS). Seventy-nine participants completed the follow-up (age 72.3±4.7, women 55.3%). An improvement in the BSRS score was found in the exercise group at 26 weeks (p=0.035) when the exercise program was concluded, and it was maintained at 48 weeks (p=0.013). No improvements were observed in the control group. To conclude, SBR, previously found as a resilience factor in older adults during COVID-19, appear to improve after a moderate 12 weeks exercise program, and the improvement persisted even after stopping exercise during the COVID-19 lockdown.